The Tree Shrew as a Model for Cancer Research - Lu, Tao; Peng, Hongmei; Zhong, Liping; Wu, Pan; He, Jian; Deng, Zhiming; Huang, Yong (Frontiers in Oncology, 2021)
Animal disease models are necessary in medical research, and an appropriate animal model is of great importance for studies about the prevention or treatment of cancer. The most important thing in the selection of animal models is to consider the similarity between animals and humans. The tree shrew (Tupaia belangeri) is a squirrel-like mammal which placed in the order Scandentia. Whole-genome sequencing has revealed that tree shrews are extremely similar to primate and humans than to rodents, with many highly conserved genes, which makes the data from studies that use tree shrews as models more convincing and the research outcomes more easily translatable. In tumour research, tree shrews are often used as animal models for hepatic and mammary cancers. As research has progressed, other types of tree shrew tumour models have been developed and exhibit clinical manifestations similar to those of humans. Combining the advantages of both rodents and primates, the tree shrew is expected to be the most powerful animal model for studying tumours.